Produktivitas Ayam Broiler dengan Pemberian Tepung Singkong Fermentasi - L Silitonga; M H Astuti; I Yuanita; S Ma'rifah; N Zega (PETERPAN (Jurnal Peternakan Terapan), 2023)
A study was conducted to investigate the effect of cassava meal fermented to productivity of broiler chickens. This study used a completely randomized design (CRD) with 4 treatments and 5 replications, each redication was filled with 3 chicks so that the number of chicks in this study was 60 chicks. The variables observed were initial weight, ration consumption, body weight gain, feed conversion, final body weight, morbidity and mortality. The treatments were P0 (research ration with 5% cassava meal), P1 (research ration with 3% cassava meal fermented), P2 (research ration with 6% cassava meal fermented), P3 (research ration with 9% cassava meal fermented). The results showed a significant difference from these facts, but not significantly different on body weight gain, ration conversion and final body weight. The average initial weight was 45.55 grams/birds, the morbidity rate were 2 chicks the mortality rate was also 0.17%. Giving cassava meal fermented up to 9% can be consumed by broiler chickens without reducing productivity.